2021
DOI: 10.3390/md19020108
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Degradation Machinery and Secondary Metabolite Profiles in the Marine Bacterium Pseudoalteromonas rubra S4059

Abstract: Genome mining of pigmented Pseudoalteromonas has revealed a large potential for the production of bioactive compounds and hydrolytic enzymes. The purpose of the present study was to explore this bioactivity potential in a potent antibiotic and enzyme producer, Pseudoalteromonas rubra strain S4059. Proteomic analyses (data are available via ProteomeXchange with identifier PXD023249) indicated that a highly efficient chitin degradation machinery was present in the red-pigmented P. rubra S4059 when grown on chiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…S5C). According to previous proteomic data on P. rubra S4059 (data are available via ProteomeXchange with identifier PXD023249), four extracellular proteases with high relative abundance were found in the samples of wild-type S4059 culture supernatants, including two peptidases ( A0A5S3UZL3 and A0A5S3V0P4 ), one putative alkaline serine protease ( A0A5S3V092 ), and a putative serine protease ( A0A5S3UW99 ) ( 20 ). The predicted molecular weights of those proteases were 53 to 64 kDa without signal peptides.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…S5C). According to previous proteomic data on P. rubra S4059 (data are available via ProteomeXchange with identifier PXD023249), four extracellular proteases with high relative abundance were found in the samples of wild-type S4059 culture supernatants, including two peptidases ( A0A5S3UZL3 and A0A5S3V0P4 ), one putative alkaline serine protease ( A0A5S3V092 ), and a putative serine protease ( A0A5S3UW99 ) ( 20 ). The predicted molecular weights of those proteases were 53 to 64 kDa without signal peptides.…”
Section: Resultsmentioning
confidence: 97%
“…Not all bacteriocins are inactivated by treatment with proteinase K and pepsin as reported for several lactic acid bacteria ( 30 ). Previous proteomic analysis on P. rubra S4059 ( 20 ) (data are available via ProteomeXchange with identifier PXD023249) indicated that the strain produced several proteases that may have the same antibacterial function as that described in P. piscicida ( 25 ). Further studies with the molecular weight cutoff and protein analyses found that the antimicrobial activities may also be due to extracellular proteases/peptidases, which were often secreted by marine bacteria and reported with potent antibacterial activity ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GH18 chitinases have been found in various organisms from bacteria to humans, including plants, molds, and vertebrates, while GH19 chitinases are found mainly in plants and are not common in bacteria, having recently been found in only a few strains, such as Chitinophaga sp. [ 4 ], Pseudoalteromonas rubra , [ 5 ], and Streptomyces alfalfa [ 6 ].…”
Section: Introductionmentioning
confidence: 99%